THE ROLE OF SOCIAL SUPPORT SYSTEMS IN ALLEVIATING THE LONELINESS FELT BY EMPLOYEES WORKING FROM HOME DURING THE COVID-19 PANDEMIC - Aulia Rachmawati; Maria Jacinta Arquisola (President University, 2021)
The year 2020 will go down as one of the hardest, most challenging periods known to man, for it is this year that millions of people succumbed to the COVID-19 pandemic. This event leads many people to stay at home to prevent and the spread of coronavirus. Therefore, everyone should stay at home that many businesses in terms of employee mandatory to work-from-home (WFH) to control the distribution of Covid-19. It leads to an increase in feeling loneliness because quarantine is isolated in a pandemic situation, where loneliness is the first problem in working from home. The study aims to find out the role that social support systems in an organization play in helping alleviate employee loneliness. Social support systems consist of Perceived Organizational Support (POS), Supervisor Support (SS), and Co-Worker Support (CS). This research used a quantitative research method with an open-ended questionnaire. A total of 137 employees that are currently working fromhome (WFH) participated in this research. By using multiple regression analysis and content analysis, the results show that co-workers' support (CS) has greater influences in alleviating the loneliness felt by the employee working from home, and the least was the perceived organization support (POS). On the whole, the social support system would be effective if organizations promote better interpersonal relationships, affiliation, and interaction with others as assigned by the organization, supervisor, and co-workers. This study provides an empirical contribution to the importance of human interactions in alleviating feelings of the loneliness felt by Indonesian employees working from home during a pandemic. Organizations must heed the call to be more engaged with their employees during this challenging situationthat affects their employees' mental and psychological state. Keywords: Employee loneliness, work-from-home (WFH), social support system, pandemic COVID-19, Indonesia